Decoding chikungunya virus non-structural protein 3 interacting partners in THP-1 derived infected macrophages through proteomic profiling - Srivastava, Priyanshu; Mishra, Nimisha; Chaudhary, Sakshi; Sunil, Sujatha (Frontiers in Virology, 2024)
Chikungunya virus (CHIKV), an alphavirus transmitted by mosquitoes, has instigated several epidemics in recent years, sparking intensive efforts to understand its biology. Despite progress, the understanding of CHIKV's molecular interactions with host cell constituents, especially in susceptible cells such as macrophages remains limited. We used a mass spectrometry platform to characterize the interactions between CHIKV-nsP3, a viral nonstructural protein, and proteins in human THP-1 macrophage cells. Our findings revealed 196 high-confidence interactions primarily involving nsP3. Further, the sub-cellular localization, and pathways these interacting proteins might be involved in were deduced using computational methods. The interacting partners were further incorporated into a comprehensive host-virus interaction network derived from extensive literature on alphavirus-host interactions. Collectively, this study offers the first interaction map between CHIKV nsP3 protein and THP-1 cells, illuminating new probable roles of host cell proteins in CHIKV's replication cycle.